Assessment of Pasteurella multocida a lipopolysaccharide, as an Adhesin in an in vitro model of rabbit respiratory epithelium (2017)
The role of the P. multocida lipopolysaccharide (LPS) as a putative adhesin during the early stages of infection with this bacterium in the respiratory epithelium of rabbits was investigated. By light microscopy and double enzyme labeling of nasal septa tissues, the amount of bacteria attached to the respiratory epithelium and the amount of LPS present in goblet cells at different experimental times were estimated. Transmission electron microscopy (TEM) and LPS labeling with colloidal gold particles were also used to determine the exact location of LPS in the cells. Septa that were challenged with LPS of P. multocida and 30 minutes later with P. multocida showed more adherent bacteria and more severe lesions than the other treatments. Free LPS was observed in the lumen of the nasal septum, forming bilamellar structures and adhering to the cilia, microvilli, cytoplasmic membrane, and cytoplasm of epithelial ciliated and goblet cells. The above findings suggest that P. multocida LPS plays an important role in the process of bacterial adhesion and that it has the ability of being internalized into host cells. ©